KAJIAN AKADEMIK TERHADAP TATA KELOLA TI DAN STRUKTURAL CIO DI PEMERINTAH DAERAH SEBAGAI IMPLEMENTASI PERATURAN MENTERI KOMUNIKASI DAN INFORMASI NOMOR 41 TAHUN 2007 - , Tri Cahyo Nugroho, Dr. Wing Wahyu Winarno, MAFIS, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The Presidential Instruction No. 3 in 2003 was the beginning of the government's commitment to implement a concept of utilization of information technology in a form of bureaucratic mechanisms are effective and efficient government, termed the Electronic Government (e-Government). Furthermore, the application of e-government guidelines related to ICT governance is set in the Regulation of the Minister of Communication and Information No. 41 in 2007, in the ministerial regulation, discusses the governance structure in order to ensure adequate capacity for leadership, and the relationship between work unit / institution synergistic government in planning, budgeting, the realization of ICT systems, ICT systems operations, and general evaluation of the implementation of ICT in government. One priority is the establishment of the entity and the CIO Committee on ICT in every institution of government. In this study there are two issues to be subject, which measures the implementation of ICT governance with local government regulations, and to the implementation of structural CIO in local government. Study of the literature on regulatory documentation, legislation and local government related organizations in charge of the ICT is a method used to determine the factors that affect the suitability of the application of ICT governance in local government. Methods of Focus Group Discussion (FGD) are used to provide recommendations on the application of ICT governance and structural CIO in local government. This research will result in a recommendation implementation steps application the Regulation of Minister of Communication and Information No. 41 of 2007 on local government.